Neovascular age‐related macular degeneration at treatment intervals of 14 weeks or greater. (14th July 2021) - Cornish, Elisa E.; Nguyen, Vuong; Young, Stephanie; Fraser‐Bell, Samantha; Guymer, Robyn; Squirrell, David; Barthelmes, Daniel; Gillies, Mark C.
Abstract: Background: We assessed the proportion of eyes with neovascular age‐related macular degeneration (nAMD) in routine clinical practice that reach ≥14 week treatment intervals and their outcomes. Method: We analysed data from the Fight Retinal Blindness! (FRB!) Project database, a prospectively designed registry of 'real‐world' outcomes. Treatment‐naive eyes starting vascular endothelial growth factor (VEGF) inhibitors for nAMD from 1st January 2006 were included. Eyes were defined to have reached the ≥14 week treatment interval if they received ≥2 consecutive injections at treatment intervals of ≥14 week but not exceeding 26 weeks. Outcomes were reported in a subgroup of eyes that had 12 months of follow‐up from reaching this interval. Results: Of the 3907 treatment‐naïve eyes that started treatment during the identified periods on a treat‐and‐extend regimen and received at least 8 injections over the first 2 years, 402 (10%) eyes received at least 2 consecutive injections at an interval of ≥14 week during their follow‐up. Fifty‐two percent of these eyes maintained vision to 12 months, however only 40% stayed at this interval and 25% of the lesions reactivated. Conclusion: We found that only 10% of eyes with nAMD were extended beyond a 13‐week injection interval and that over half had returned to a shorter interval by 12 months. Eyes that stayed at this extended treatment interval maintained stable vision. More data on the outcomes of eyes treated with intervals longer than 3 months are required to establish whether emerging VEGF inhibitors provide a more sustained effect than the currently available drugs.